150k views
4 votes
Create an equation with one solution of x = −1.

10x − (x − 6) = 2x − ( ? + x)

1 Answer

1 vote

Answer:

?=2

Explanation:

10)(−1)−(−1−6)=(2)(−1)−(x−1)

Simplify both sides of the equation.

(10)(−1)−(−1−6)=(2)(−1)−(x−1)

(10)(−1)+−1(−1−6)=(2)(−1)+−1(x−1)

(10)(−1)+(−1)(−1)+(−1)(−6)=(2)(−1)+−1x+(−1)(−1)

(10)(−1)+1+6=(2)(−1)+−x+1

−10+1+6=−2+−x+1

(−10+1+6)=(−x)+(−2+1)

−3=−x+−1

−3=−x−1

Flip the equation.

−x−1=−3

Add 1 to both sides.

−x−1+1=−3+1

−x=−2

Divide both sides by -1.

−x

−1

=

−2

−1

x=2

User Webpreneur
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.